STRATEGIC IMPORTANCE OF ANCIENT INDIAN MARITIME POWER - Mishra, Vivek Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is a peninsular country bounded by the lofty Himalayas in the north, is surrounded by oceans and seas on three sides and has a 7,517 km long coastline. The Indian Ocean engulfs the country in its South. It has recently re-emerged as a sphere of power politics in International Relations. The following slok of Vishnu Purana illustrates the Geo-Strategic importance of Bharat. उत्तरं यत् समुद्रस्य हिमाद्रेश्चैव दक्षिणम् | वर्षं तद् भारतं नाम भारती यत्र सन्ततिः || विष्णु पुराण २.३.१ The country that lies north of the ocean and south of the snowy mountains is called Bhāratam, there dwells the descendants of Bharat. China is in India’s backyard, an expansionist and imperialist power challenging the aspects of maritime security in the region, and Pakistan is a hostile neighbour, it is high time that a comprehensive framework of India’s maritime security is developed. As an ancient civilisation, the country has a rich legacy of its naval prowess. The civilisational culture from the ancient land of Bharat spread worldwide, especially in Southeast Asian, African, Central Asian, and East Asian countries through the Indian Ocean. The Indian Ocean, therefore, is not merely a waterbody. Instead, it captures the essence of India’s religion and cultural wave, transcending even to the neighbouring countries. India’s history, art, mythology and literature are replete with numerous instances of the importance of the Indian Ocean in the lives of the Indian people. The cultural depth of the Indian civilisation is as deep as the Indian Ocean. Therefore, this article argues about the strategic relevance of ancient India’s maritime diplomacy.